Capacity Development-oriented Service Delivery Structures and Programmes: Case Study of a Mineral-rich District Municipality - Mphahlele, Matuku; Lucas Zandamela, Horacio; Zandamela, Lucas (Journal of Public Administration and Governance, 2023)
Bojanala Platinum District Municipality (BPDM), in the North-West Province, South Africa, is endowed with an extractive economy. The District experiences challenges of capacity development of service delivery structures and programmes. It is in this context that this paper examines how local government responses to challenges of capacity development and explores ways in which organisational structures and programmes can be used to overcome these challenges for enhanced service delivery. The theoretical framing of this study underpins capacity development as an enabler of service delivery and incorporates human capital, performance improvement and collaborative participation in the context of local government. The research employed a single case qualitative research approach with a component of descriptive statistics and a sample of 30 municipal senior managers and a social development mine manager. Key findings are that organisational learning and skills development play important roles in enhancing the capacity development of service delivery structures and programmes. It is against these findings that the study recommends the creation of supportive monitoring and evaluation systems to advance the strengthening of functional hybrid governance structures and an organic communication model within a transparent and accountable administrative-political environment.